System identification of inventory system using ARX and ARMAX models - Sofia Rachad; Benayad Nsiri; Bahloul Bensassi (My University, 2015)
This paper presents a mathematical model of an inventory system from the warehouse of goods Distribution Company using system identification approach. Considering items ordered from suppliers and items shipped to customers, as the inputs of the system and the stock level as the output system. In this paper, ARX model and ARMAX model are outlined and compared. The performances of each type of model are highlighted. A case study with real data set is discussed.
Keywords: System identification; inventory system; Stock level; ARX model; ARMAX model